PEGylation of Deferoxamine for Improving the Stability, Cytotoxicity, and Iron-Overload in an Experimental Stroke Model in Rats - Xu, Jiake; Sun, Tong; Zhong, Rui; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
Deferoxamine (DFO) is a widely used drug for the treatment of iron-overload related diseases in clinic. However, its inherent shortcomings such as short plasma half-life and cytotoxicity remain to be addressed to widen its clinical utility. In this work, PEGylated DFO was first synthesized and its chemical structure was characterized, and then in vitro and in vivo studies were carried out. The metabolism assay showed that the stability of the PEGylated DFO was significantly improved, with half-life more than 20 times longer than that of the DFO. Furthermore, the PEGylated DFO exhibited significantly lower cytotoxicity than that of the DFO, and also the hemocompatibility assay showed that the PEGylated DFO had no significant effect on the coagulation system, red blood cells, complement, and platelet. In vivo studies indicated that PEGylated DFO was capable of reducing the iron accumulation, degeneration of neurons, and promoting functional recovery. Taken together, PEGylated DFO improved stability, cytotoxicity, and iron-overload in an experimental stroke model in rat, making it promising for application in treating iron-overload conditions in the clinic.